Twisted twenty-six - Evanovich, Janet (New York : G.P. Putnam's Sons, 2019)
Grandma Mazur is a widow...again. The unlucky groom was one Jimmy Rosolli, local gangster and lothario. At least Grandma can have all the attention she wants as the dutiful widow. But some kinds of attention are not welcomed, particularly from Jimmy's former "business partners". As someone who has spent an entire career finding bad guys, helping Grandma Mazur should be no challenge for Stephanie Plum.
2nd to last book in the series.
Keywords: Plum, Stephanie -- (Fictitious character) -- Fiction; Women private investigators -- Fiction; Women bounty hunters -- Fiction; Trenton (N.J.) -- Fiction; Detective and mystery fiction